2015
DOI: 10.12659/msm.895380
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 (896A/G and 1196C/T) Gene Polymorphisms with Asthma Risk: A Meta-Analysis

Abstract: BackgroundConflicting data have been reported on the association between Toll-like receptor 4 (TLR4) +896A/G and +1196C/T polymorphisms and the risk of asthma. Therefore, we conducted this meta-analysis to clarify the effect of TLR4 +896A/G and +1196C/T polymorphisms on the risk of asthma.Material/MethodsAn electronic literature search was performed using PubMed, Embase, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wanfang Data to find relevant studies. Odds ratios (ORs) and 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…A recent meta-analysis performed by Li et al revealed a significant association between TLR4 1196C/T polymorphism and asthma patients, but not with the 896A/G polymorphism. 62 Similar results have also been reported by Yao et al 63 and Sinha et al 64 in North Indians. Zhang et al further genotyped individuals with asthma for TLR4 variants to make comparison with asthma severity and T cell subpopulations and found that variant rs1927907 may be related to asthma severity and the degree of TLR4 expression on the surface of Tregs.…”
Section: Cellular Mediators Of Inflammation In Asthma Airway Epitheliumsupporting
confidence: 85%
“…A recent meta-analysis performed by Li et al revealed a significant association between TLR4 1196C/T polymorphism and asthma patients, but not with the 896A/G polymorphism. 62 Similar results have also been reported by Yao et al 63 and Sinha et al 64 in North Indians. Zhang et al further genotyped individuals with asthma for TLR4 variants to make comparison with asthma severity and T cell subpopulations and found that variant rs1927907 may be related to asthma severity and the degree of TLR4 expression on the surface of Tregs.…”
Section: Cellular Mediators Of Inflammation In Asthma Airway Epitheliumsupporting
confidence: 85%
“…MPL is a component of the adjuvant Pollinex Quattro, which has undergone randomised clinical trials in allergic rhinitis in man. However, there is not a clear indication as to the role of TLR4 in asthma nor atopic diseases, with meta-analyses having identified that TLR4 polymorphisms may be either preventative ( 79 ) or represent risk factors ( 53 ) for development of asthma while TLR4 protein levels are enhanced in the nasal mucosa of patients with allergic rhinitis ( 55 ). Whilst MPL has been used clinically as an adjuvant, lipopolysaccharide (LPS) has been used in the majority of in vitro and animal mechanistic studies.…”
Section: Extracellular Tlrsmentioning
confidence: 99%
“…In support of these findings, interruption of the clotting system by administering anticoagulants such as heparin has previously been shown to be beneficial in asthma [47,48]. Additionally, TLR4 impacts the expression of asthma in complex ways, such that multiple TLR4 ligands have been shown to enhance disease expression in mice [25,39,49] and TLR4 polymorphisms confer either enhanced [50] or reduced [51] asthma susceptibility. Th2 and Th17 cell activation, through antigen presentation by dendritic cells, but usually without inducing disease.…”
Section: Proteolytic Induction Of Type 2 Immunitymentioning
confidence: 84%